Brain Network Organization and Social Executive Performance in Frontotemporal Dementia. (18th February 2016) - Sedeño, Lucas; Couto, Blas; García-Cordero, Indira; Melloni, Margherita; Baez, Sandra; Morales Sepúlveda, Juan Pablo; Fraiman, Daniel; Huepe, David; Hurtado, Esteban; Matallana, Diana; Kuljis, Rodrigo; Torralva, Teresa; et al.
Abstract: Objectives: Behavioral variant frontotemporal dementia (bvFTD) is characterized by early atrophy in the frontotemporoinsular regions. These regions overlap with networks that are engaged in social cognition-executive functions, two hallmarks deficits of bvFTD. We examine (i) whether Network Centrality (a graph theory metric that measures how important a node is in a brain network) in the frontotemporoinsular network is disrupted in bvFTD, and (ii) the level of involvement of this network in social-executive performance.Methods: Patients with probable bvFTD, healthy controls, and frontoinsular stroke patients underwent functional MRI resting-state recordings and completed social-executive behavioral measures.Results: Relative to the controls and the stroke group, the bvFTD patients presented decreased Network Centrality. In addition, this measure was associated with social cognition and executive functions. To test the specificity of these results for the Network Centrality of the frontotemporoinsular network, we assessed the main areas from six resting-state networks. No group differences or behavioral associations were found in these networks. Finally, Network Centrality and behavior distinguished bvFTD patients from the other groups with a high classification rate.Conclusions: bvFTD selectively affects Network Centrality in the frontotemporoinsular network, which is associated with high-level social and executive profile. ( JINS, 2016, 22, 250–262)